Development of an automatic storage and retrieval system for handling pallets with dynamic positioning - Oluwatoyin, Shobowale Kafayat (Kulliyyah of Engineering, International Islamic University Malaysia, 2010)
Storage and Retrieval (SR) machines, racks and pallets are the principal components of the modern Automatic Storage and Retrieval Systems (AS/RS). Traditionally, passages are left between two sets of racks for smooth traveling of the SR machines, which are in most of the cases Fork Lifts that travel between the Input / Output (I/O) stations and the storage locations. Space occupied by an AS/RS is almost double the space of the goods stored. In this research, an AS/RS is designed that looks like a puzzle or Sudoku where the pallets are arranged in a matrix form, leaving one empty space as I/O station instead of passages between the pallets. SR machines are replaced by a new mechanical system consisting of racks at the underside of the pallets, and special arrangement of pinions along with direct current geared motors is mounted on the floor. This mechanical system is capable of moving the pallets over the spaces along two orthogonal directions in a single plane independently. During storage as well as retrieval operations, some or all the pallets change their addresses, unlike the traditional AS/RS. Limit switches are used to keep track of the positions of the pallets changing addresses dynamically. A modified A-star heuristic algorithm is used for finding the shortest route, store and retrieve specific pallet. Two Microcontrollers (PIC 16F877A) are used as the controller and serial peripheral interface (SPI) as the communication protocol and finally a graphical user interface is developed for user control. The performances of the system are evaluated through simulation of a 3×3 matrix and then verified experimentally with a 2×2 matrix successfully. This new AS/RS is capable of reducing space requirement by more than 50 percent. Automation of car parking is expected to be one of the target applications of this new AS/RS. This system however, needs further research to optimize the matrix size as well as to minimize the number of actuators, which are motors.